Integer Programming Based Methods Applied to Cutting, Packing, and Scheduling - Lima, Vinícius L. de; Queiroz, Thiago A. de; Miyazawa, Flávio K. (Anais do Concurso de Teses e Dissertações da SBC (CTD-SBC), 2022)
We propose many contributions related to combinatorial optimization. First, we propose a number of exact methods for a general class of integer programming models, allowing applications to several important combinatorial optimization problems. To evaluate the effectiveness of our methods, we apply them to many well-studied cutting, packing, and scheduling problems, including the classical bin packing problem. The proposed methods could solve a large number of open benchmark instances, becoming the leading algorithms and the new state-of-the-art of all these problems. We also propose contributions to facilitate future research on two-dimensional cutting and packing. Lastly, we solve a complex problem arisen from a real-world case study in the food industry.